(3GdebUhQ hGdeeOhOs - (3ZdGe KYdH , eMeO Hf YHO GdhGMO Hf CHj gGTe GdeWQR, CHh YeQ,J (B345 (3g` s
(3ChdgG (B:s
(3GdMQha GdebUhQI (B: (3ghi GdfaS hfOi GdCQV s
(3BNQgG (B:s
(3hGdHGbdG hGdHGbdi hGdeQYRG hGdeQYRi hGdbHjWG hGdbHjWi EPG NaVf eOOf hEPG TOOf bUQf hcJHf HGdjGA Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B266s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(100 / 9 (3b(B) s
Keywords: (3GddZIs